Impact of DC link faults on the performance of full converter based WECS - Yunus, A.; Abu Siada, Ahmed; Masoum, Mohammad Sherkat; Islam, Syed (Faculty of Engineering, Alexandria University, 2012)
The number of full converter based wind energy conversion system (FCWECS) connected to the electricity grids have increased significantly worldwide during the last decade. This triggers off manufactures to improve the performance of FCWECS through robust and reliable designs. FCWECS is interfaced with the grid through voltage source inverter (VSI) and rectifier which are considered as the crux of the FCWECS system. The VSI determines the ability of wind turbine to operate optimally during wind speed fluctuation and it can provide reactive power support to the grid during grid disturbance events. The DC capacitor link between the rectifier and the VSI allows optimum and smooth power transfer between FCWECS and the grid. Therefore, any faults within the DC link will affect the overall performance of the FCWECS. This paper investigates the impact of short circuit and open circuit faults across the DC link capacitor on the dynamic performance of the FCWECS. The compliance of the wind energy conversion system (WECS) with different grid codes such as those of Denmark, Spain, Nordic and Sweden under such faults is also investigated.